Promotion of Reading Skills with a Recipient and Domain Specific Focus - Empirical Findings in the Professional Field of Construction Engineering - Rexing, Volker [Verfasser]; Keimes, Christina [Verfasser]; Ziegler, Birgit [Verfasser] (My University, 2015)
"Up-to-date efforts to promote reading skills in vocational education have had little effect. The motivational attitude of apprentices towards reading is proving to be a challenge. It is clear that a lot of apprentices remain unaware of the importance of reading competence to their professional lives. Accordingly the consequences for effective training concepts to promote reading skills result from a systematic analysis of the professional (training) reality in the vocational field of construction engineering. In such training concepts the discrepancy between pedagogical objectives and the low value ascribed to reading skills by the trainees seems to be the key didactical challenge. Another important conclusion is the conceptual design of recipient- and domain-specific promotion of reading skills." (author's abstract)

"Zur Wirksamkeit von Lesekompetenzförderung im berufsbildenden Kontext liegen bisher eher negative Befunde vor. Als bedeutungsvoll zeigt sich vor allem die problematische motivationale Einstellung zum Lesen. Offensichtlich wird die berufliche Relevanz von Lesekompetenz vielen Auszubildenden nicht deutlich. Auf Basis einer Untersuchung der betrieblichen (Ausbildungs-)Realität im Berufsfeld Bautechnik werden Konsequenzen für eine effektive Lesekompetenzförderung formuliert. Dabei erscheint insbesondere die Diskrepanz zwischen pädagogischer Intention und geringer Relevanzzuschreibung als zentrale didaktische Herausforderung. Darüber hinaus zeigt sich die Bedeutung einer adressaten- und domänenspezifischen Förderung von Lesekompetenz." (Autorenreferat, BIBB-Doku)
Förderung von Lesekompetenz - Herausforderungen im Berufsfeld Bautechnik
Keywords: L 3 Lehr-Lern-Forschung; S 6.2.6 Hoch- und Tiefbauberufe; Berufsbildung; Lesekompetenz; Förderung; Berufsfeld Bautechnik